The Role of Digital Zakat in Enhancing National Income: A Qualitative Review from the Indonesian Context - Wildan Hadi; Erizal Candra Efendi; Ruri Mustika; Hafni Juniyanti Hsb; Fitriani (Al-bank: Journal of Islamic Banking and Finance, 2026)
This study analyzes the role of digital zakat in enhancing national income within the Indonesian context using a qualitative literature-based approach. Secondary data were collected from peer-reviewed journal articles, policy reports, and credible digital sources indexed in platforms such as Google Scholar and POP. The analysis was conducted through thematic synthesis to identify recurring patterns and mechanisms linking digital zakat practices to macroeconomic outcomes.The findings indicate that digital zakat contributes to national income through three main mechanisms. First, digital platforms increase zakat collection efficiency by expanding the number of contributors and reducing transaction costs, which leads to higher aggregate zakat funds. Second, the faster and more transparent distribution of zakat funds stimulates household consumption among beneficiaries, particularly for basic needs such as food, education, and health services. Third, digital zakat supports micro and small enterprises through productive zakat schemes, enabling income generation and local economic circulation. In this study, the term “significant role” refers to the consistent evidence across multiple studies showing that digital zakat enhances economic participation, improves income distribution, and strengthens the microeconomic sector, rather than to statistical significance. Overall, digital zakat functions as a complementary socio-economic instrument that supports national income growth while promoting social welfare and financial inclusion